Building occupancy estimation using Markov chain - Boey, Timothy Shao Xuan (Nanyang Technological University, 2021)
Building Occupancy estimation has been one of the major challenges for energy conservation due to its large amount of energy consumption. Reports show that households account for 14.9% of energy consumption in Singapore for the year 2019. [1] This project aims to estimate the occupancy level for a 4-man HDB household using a inhomogeneous Markov Chain for the MOSZ and MOMZ cases. In this project, the state of the Markov Model depends on the change in occupancy instead of the usual current occupancy count. The change in occupancy is calculated by calculating the net change in occupancy for the hour.